2014
DOI: 10.1097/ftd.0000000000000056
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Performance of a Gentamicin Population Pharmacokinetic Model in Neonates Receiving Full-Body Hypothermia

Abstract: Background Population pharmacokinetic (popPK) models derived from small PK studies in neonates are often underpowered to detect clinically important characteristics that drive dosing. External validation of such models is crucial. In this study, the predictive performance of a gentamicin popPK model in neonates receiving hypothermia was evaluated. Methods A previously published gentamicin popPK model was developed in neonates with hypoxic ischemic encephalopathy undergoing hypothermia using a retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
1
24
1
Order By: Relevance
“…However, the CL values between the two investigations were notably different with an estimate of 1 ml/minute/kg versus 2.2 ml/minute/kg, respectively . Both of the CL estimates are higher than previously reported in neonates with HIE receiving CH, in normothermic neonates with HIE, and normothermic neonates without HIE with CL ranges reported from 0.4–0.8 ml/minute/kg . Interestingly, the two prospective pharmacokinetic investigations found CH to increase the CL of gentamicin.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…However, the CL values between the two investigations were notably different with an estimate of 1 ml/minute/kg versus 2.2 ml/minute/kg, respectively . Both of the CL estimates are higher than previously reported in neonates with HIE receiving CH, in normothermic neonates with HIE, and normothermic neonates without HIE with CL ranges reported from 0.4–0.8 ml/minute/kg . Interestingly, the two prospective pharmacokinetic investigations found CH to increase the CL of gentamicin.…”
Section: Discussioncontrasting
confidence: 59%
“…Given the potential adverse effects of gentamicin on auditory and renal function, additional data describing the pharmacokinetics and resulting pharmacodynamics in the setting of CH were undertaken. Most of the available literature to date retrospectively evaluated gentamicin peak and/or trough serum concentrations . One study reported no difference in gentamicin trough concentrations between cooled and normothermic neonates with HIE .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measured creatinine Cl that involves 24‐hour urine collection would yield more accurate results, but the method is not applicable in routine clinical practice in paediatric intensive care units. Special attention should be given to newborns whose serum creatinine concentrations also reflect the maternal renal function and maternal creatinine because serum creatinine is transported across the placenta in both directions . In newborns and infants, the renal function changes due to maturation, but older paediatric patients submitted to intensive care units can also have considerably reduced renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The bias and precision of clearance prediction were assessed through calculation of average fold error (AFE) and absolute average fold error (AAFE) using the following: AFE=101NΣlog(CLpredictedCLobserved) AAFE=101NΣ(logCLpredictedCLobserved) where N denotes the number of neonates in the neonatal trial. An AFE greater than 1 suggests a bias toward overprediction, and an AFE less than 1 suggests a bias toward underprediction.…”
Section: Methodsmentioning
confidence: 99%